Discovery of flat seismic reflections in the mantle beneath the young Juan de Fuca Plate - Yanfang Qin (Nature Portfolio, 2020)
Applying seismic imaging methods on ocean bottom hydrophone data, the authors here describe a horizontal, flat lithosphere base plus lithosphere-asthenosphere boundary beneath the young (0.51 to 2.67 Ma) Juan de Fuca plate.